Ellagic acid protects against non-alcoholic fatty liver disease in streptozotocin-diabetic rats by activating AMPK - Jozaa Z. ALTamimi; Ghedeir M. Alshammari; Nora A. AlFaris; Reham I. Alagal; Dalal H. Aljabryn; Norah A. Albekairi; Mahmoud Ahmad Alkhateeb; Mohammed Abdo Yahya (Taylor & Francis Group, 2022)
Context Ellagic acid (EA) is used in traditional medicine to treated hyperlipidaemia. Objective This study examined if AMPK mediates the anti-steatotic effect of ellagic acid (EA) in streptozotocin (STZ)-induced type 1 diabetes mellitus in rats. Materials and methods Adult male Wistar rats (130 ± 10 g) were divided into 6 groups (n = 8 rats/group) as control, control + EA, control + EA + CC an AMPK inhibitor), T1DM, T1DM + EA, and T1DM + EA + CC. The treatments with EA (50 mg/kg/orally) and CC (200 ng/rat/i.p.) were given the desired groups for 12 weeks, daily. Results In T1DM-rats, EA reduced fasting glucose levels (44.8%), increased fasting insulin levels (92.8%), prevented hepatic lipid accumulation, and decreased hepatic and serum levels of total triglycerides (54% & 61%), cholesterol (57% & 48%), and free fatty acids (40% & 37%). It also reduced hepatic levels of ROS (62%), MDA (52%), TNF-α (62%), and IL-6 (57.2%) and the nuclear activity of NF-κB p65 (54%) but increased the nuclear activity of Nrf-2 (4-fold) and levels of GSH (107%) and SOD (87%). Besides, EA reduced downregulated SREBP1 (35%), SREBP2 (34%), ACC-1 (36%), FAS (38%), and HMG-CoAR (49%) but stimulated mRNA levels of PPARα (1.7-fold) and CPT1a (1.8-fold), CPT1b (2.9-fold), and p-AMPK (4-fold). All these events were prevented by the co-administration of CC. Discussion and conclusions These findings encourage the use of EA to treat hepatic disorders, and non-alcoholic fatty liver disease (NAFLD). Further in vivo and in vitro studies are needed to validate its potential in clinical medicine.